Touch gesture authentication framework for touch screen mobile devices - Alariki, Ala Abdulhakim (Asian Research Publishing Network (ARPN), 2014)
With the increased popularity of touchscreen mobile phones, touch gesture behavior is becoming more and more important. Increasing demand for safer access in touch screen mobile phones, ancient strategies like pins, tokens, or passwords fail to stay up with the challenges conferred. Most of the current touch gesture authentication schemes facing problem with accuracy based on score classifiers of EER, FAR and FRR. In addition, collecting touch duration feature only may not be able to achieve the desired authentication accuracy and robustness. However, gathering more touch features such as finger pressure, finger size and acceleration would help to get a better authentication accuracy and verification performance. These efforts have allowed us to provide a comprehensive summary of recent work on touch behavior authentication and a frame work to implement the system. Finally, we conclude the future work in this topic which is implement and test the framework of touch gesture gesture-based behavioral biometrics and obtain more accuracy and robustness authentication system.